Papel da conexina-43 e panexina-1 na infecção por Clostridioides difficile e na morte celular e suprarregulação de il-6 promovidas pelas toxinas A e B - Loureiro, Andréa Viana (2021)
Clostridioides difficile (C. difficile), a gram-positive anaerobic spore-forming bacillus, is a major cause of nosocomial diarrhea associated with the use of antibiotics. C. difficile produces toxin A (TcdA) and B (TcdB), both associated with intestinal damage caused by this anaerobic. Connexin-43 (Cx43) and Pannexin-1 (Panx1), which can be expressed by a variety of cells, allow the passage of messenger molecules regulating the inflammatory process. The effect of TcdA or TcdB on Cx43 and Panx1 expression in enteric glial cells (EGCs), as well as their role in the deleterious effects of these toxins is still unclear in the literature. Thus, this study aims to verify changes induced by C. difficile infection (CDI) in the expression of Cx43 and Panx1 in the colon and cecum of infected animals, as well as to investigate the role of these channels in cell death and expression of IL-6 induced by TcdA and TcdB in EGCs. C57BL/6 male mice (8 weeks old) were infected with C. difficile VPI10463 (105 CFU in Chopped Meat broth - CPP/animal via gavage), and control group received only CPP via gavage. After three days of infection, samples of cecum and colon were collected to evaluate the expression of Cx43 and Panx-1 by immunohistochemistry. In vitro, EGCs lineage (PK060399egfr) were challenged with TcdA (50 ng/mL) and TcdB (1 ng/mL), in the presence or absence of Cx43 (Gap19 trifluoroacetate, 1 and 10 µM) and Panx1 (10Panx trifluoroacetate, 10 and 50 µM) inhibitors for 2, 12 and/or 18h. After this, the following parameters were evaluated: expression of Cx43 and Panx1 (Western blotting and qPCR), analysis of caspase-3 activity and phosphatidylserine annexin-V binding by luminescence assay, as well as IL-6 expression (qPCR). CDI significantly increased the levels of Cx43 in cecum (p = 0.03) and Panx1 in cecum (p = 0.01) and colon (p = 0.04) of mice compared to the control group. In vitro, TcdA, but not TcdB, upregulated Cx43 in EGCs in 2h. The inhibition of Cx43 did not reduce the caspase-3 activity induced by both toxins, however decreased IL-6 gene expression induced by TcdB (p = 0.0001), but not by TcdA. In relation to Panx1, TcdA and TcdB significantly increased its gene expression after 18h of incubation. Panx1 inhibitor (50 µM) decreased caspase-3 activity (p = 0.002) and phosphatidylserine-annexin-V binding (p = 0.001), but not IL-6 gene expression in TcdA and TcdB-challenged EGCs. In conclusion, Cx43 and Panx1, which are increased during CDI, play an important role in the effects of C. difficile toxins in EGCs, Cx43 promoting the expression of IL-6 induced by TcdB and Panx1, in turn, participating in cell death induced by both toxins in EGCs